ON THE PROPAGATION OF RADIO EMISSION IN THE CROWN OF THE QUIET SUN WITH MAGNETIC FIELD - Tsvyk, N. (Одеські астрономічні публікації, 2013)
There are searching for factors that influence on the brightness temperature distribution of the quiet Sun at decameter radio waves which may explain the ellipsoidal shape and other features in the radio brightness profile.